Stranger in a Strange land: Aspiration, Uniform and the fine Edges of Identity - O'Sullivan, Sandy (Wakefield Press, 2015)
Colouring the Rainbow uncovers the often hidden world of Queer and Trans Blak Australia and tells it like it is. Twenty-two First Nations people reveal their inner reflections and outlooks on family and culture, identity and respect, homophobia, transphobia, racism and decolonisation, activism, art, performance and more, through life stories and essays. The contributors to this ground-breaking book not only record the continuing relevance of traditional culture and practices, they also explain the emergence of homonormativity within the context of contemporary settler colonialism. Colouring the Rainbow is a real, searing and celebratory exploration of modern culture in post-apology Australia. [Book Synopsis]